No advantage of single day 6 good-quality blastocyst transfer versus single day 5 poor-quality blastocyst transfer in frozen-thawed cycles stratified by age: a retrospective study - Yuxia He; Yan Tang; Haiying Liu; Jianqiao Liu; Yuling Mao (BMC, 2023)
Abstract Background Blastocyst developmental speed, morphological grading and patient age are associated with pregnancy outcomes of frozen-thawed cycles. This study aimed to compare the clinical and neonatal outcomes between poor-quality D5 blastocysts and good-quality D6 blastocysts stratified by patient age. Methods A total of 1,623 cycles were divided into two groups: group A (n = 723) received one D5 poor-quality blastocyst; group B (n = 900) received one D6 good-quality blastocyst. Pregnancy and neonatal outcomes were compared among the four groups stratified by 35 years of age. Results When patients were in the same age group, there was no significant difference in terms of age, body mass index, infertility duration, infertility type, fertilization method, proportion of endometrial preparation protocols, and endometrial thickness between D5 poor-quality and D6 high-quality blastocysts groups. Live birth rate of D5 poor-quality blastocysts was higher than that of D6 high-quality blastocysts for patients aged < 35 years (35.48% vs. 31.13%, p > 0.05), but there was no statistical difference. The same trend was showed for patients aged ≥ 35 years (29.09% vs. 21.28%, p > 0.05). Moreover, when patients were in the same age category, there was no significant difference in terms of gestational age, birth weight, birth height, and rates of preterm birth, low birth weight, and very low birth weight between groups A and B. Conclusions The preferential selection of poor-quality D5 blastocysts for transfer compared to high-quality D6 blastocysts is recommended, especially for advanced age patients. Single good-quality D6 blastocyst transfer can be considered for the acceptable live birth rate.